2008
DOI: 10.1158/1055-9965.epi-07-2660
|View full text |Cite
|
Sign up to set email alerts
|

Serum β-Glucuronidase Activity in Response to Fruit and Vegetable Supplementation: A Controlled Feeding Study

Abstract: Background: Fruit and vegetable (F&V) intake may lower the risk of some cancers. One hypothesized, but understudied, chemopreventive mechanism is that plant food constituents inhibit B-glucuronidase, an acid hydrolase that deconjugates glucuronides. Methods: We conducted a crossover feeding trial in 63 healthy women and men ages 20 to 40 years to examine the effect of diet on serum B-glucuronidase activity. Participants were randomized to two 2-week experimental diets with an intervening washout period: a diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Previously, we conducted a cross-sectional pilot study of 83 men and 120 women (22) and observed weak inverse associations between intakes of plant foods and nutrients and serum β-glucuronidase activity. In a subsequent controlled feeding study, we observed no β-glucuronidase lowering effect from supplementation of 10 servings/d of soy, citrus fruits and cruciferous vegetables (23). With respect to non-dietary factors, β-glucuronidase has been positively associated with males, increased age, and higher BMI; however, results have been based on a few, small-sampled studies (1).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previously, we conducted a cross-sectional pilot study of 83 men and 120 women (22) and observed weak inverse associations between intakes of plant foods and nutrients and serum β-glucuronidase activity. In a subsequent controlled feeding study, we observed no β-glucuronidase lowering effect from supplementation of 10 servings/d of soy, citrus fruits and cruciferous vegetables (23). With respect to non-dietary factors, β-glucuronidase has been positively associated with males, increased age, and higher BMI; however, results have been based on a few, small-sampled studies (1).…”
Section: Introductionmentioning
confidence: 83%
“…Participants completed an eligibility questionnaire and because this sample was the basis of recruitment for a subsequent dietary feeding study (23), individuals were excluded for the following reasons: 1) medical history of gastrointestinal, hepatic or renal disorders; 2) current or planned pregnancy or lactation; 3) major dietary and/or weight change (>4.5 kg) in the past year; 4) antibiotic use within the past 3 months; 5) BMI >30 or <18; 6) current use of over-the-counter, recreational and prescription drugs (including oral contraceptives); 7) regular exposure (including occupational) to passive smoke or organic solvents; 8) alcohol intake >2 drinks/day (720 mL beer, 240 mL wine or 90 mL hard liquor); 9) no interest in participating in the subsequent controlled feeding trial of fruits and vegetables; and, 10) exercise regimens that require or result in significant short-term dietary changes. Additionally, participants were asked to discontinue use of all multivitamins and dietary supplements one week before participating in the study.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of ˇ-glucuronidase activity ␤-Glucuronidase activity was measured by a colorimetric analysis using phenolphthalein mono-␤-glucuronide as the substrate [29]. Briefly, plasma (50 L) was incubated with 1 mM phenolphthalein glucuronic acid in 0.1 mM sodium phosphate buffer at pH 4.5 for 4 h at 37 • C. At 4 h, the reaction was stopped by adding 0.1 M sodium phosphate buffer pH 11.…”
Section: Analysis Of Quercetin and Metabolites In Plasmamentioning
confidence: 99%
“…In this case, a small amount of GlcA-terminated chains could be rationalized by decreased β-glucuronidase activity across the pool or in one or more individuals whose plasma was in the pooled sample used in the present study. It has been shown that β-glucuronidase activity varies greatly between healthy individuals due to the different levels of enzyme expression and environmental factors, such as dietary preferences [39, 40]. The reason for the absence of even-number chains in the urinary bikunin GAG could have been an artifact of the analysis: it is virtually impossible to detect a minor component in a mixture of hundred components each of which exhibits multiple charge states and various degrees of Na substitution.…”
Section: Resultsmentioning
confidence: 99%